2021
DOI: 10.20945/2359-3997000000362
|View full text |Cite
|
Sign up to set email alerts
|

Medical adherence in the time of social distancing: a brief report on the impact of the COVID-19 pandemic on adherence to treatment in patients with diabetes

Abstract: We conducted a cross-sectional study to evaluate the impact of social distancing determined by the COVID-19 pandemic on treatment adherence using the Self-Care Inventory-revised in adults with diabetes mellitus. In type 1 diabetes, the adherence score was lower during than before social distancing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
(13 reference statements)
2
6
0
Order By: Relevance
“…For the articles that reported a time period of data collection, dates ranged from March 2020 to April 2021, though Rowlands et al (35) had baseline data dating back to 2017. One study in Brazil compared data from a sample of people with diabetes during COVID-19 to data from an age-matched sample of people with diabetes in 2016 (37). The remainder (n=15) of studies asked participants to report their current health behaviors and also to recall their pre-COVID-19 health behaviors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the articles that reported a time period of data collection, dates ranged from March 2020 to April 2021, though Rowlands et al (35) had baseline data dating back to 2017. One study in Brazil compared data from a sample of people with diabetes during COVID-19 to data from an age-matched sample of people with diabetes in 2016 (37). The remainder (n=15) of studies asked participants to report their current health behaviors and also to recall their pre-COVID-19 health behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies examined global diabetes self-care scores. One study reported no change (37) and two studies (59,60) reported decreased total diabetes self-care scores. Silva-Tinoco et al (59) found that higher pre-pandemic self-care was related to fewer problems with self-care during the pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding diabetes care, we found an improvement in self-care scores and treatment adherence among participants with type 1 diabetes throughout the pandemic. Franco et al (2021) assessed treatment adherence in the first months of the pandemic and found a worsening in adherence scores among patients with type 1 diabetes compared to the pre-pandemic period. It is possible that the beginning of the pandemic and the consequences of social distancing have negatively affected these patients, and also that, over time, they have become more resilient and strengthened their support networks, improving self-care.…”
Section: Discussionmentioning
confidence: 99%
“…In many countries, the COVID-19 pandemic poses a great public health threat. Social distancing restrictions can increase the lack of social connection, enhance sense of loneliness (Holmes et al, 2020;Lippke et al, 2021) and decrease medical adherence in patients with chronic illness (Franco et al, 2021). Patients with CHD, who are especially susceptible to loneliness, are likely to experience more severe loneliness during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%